POSSIBLE ADOPTION OF TRIZ AND FEA FOR ENHANCING PINEAPPLE LEAF FIBER EXTRACTOR MACHINE PERFORMANCE: A MINI REVIEW - Muhammad Imran Najeeb; Mohamed Thariq Bin Haji Hameed Sultan; Farah Syazwani Shahar (Journal of Rural Development and Applied Technology, 2024)
Pineapple fibres have the potential to be used in a variety of industrial applications; however, the laborious procedure required to separate fibres from pineapple leaves prevents their utilisation to their full potential. Extracting fibres from leaves using the machines which are at present available is an inefficient process because it requires much time to complete. In this study, we discuss the 'Theoria Resheneyva Isobretatelskehuh Zadach' (TRIZ) approach and the contribution that finite element analysis (FEA) made to the development of a product innovation. In the future, this research may be used to improve existing pineapple extractor machines. It is suggested that by combining both TRIZ and finite element analysis are able to fasten the research and development process to a better pineapple extraction machine.